Meningkatkan Kewirausahaan Mahasiswa melalui Pemberdayaan Kearifan Lokal di Masyarakat Bangko - Kusaimah; Dahri, Muhtar; Putri, Zilvina (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2025)
This community service program aims to enhance the entrepreneurial skills of Law Faculty students at Merangin University through the empowerment of local wisdom in Bangko. The method used is a participatory approach with training, mentoring, and collaboration with the local community. The results show that students successfully developed competitive products based on local wisdom. The main challenges faced include limited knowledge of business management and digital marketing. However, through comprehensive empowerment strategies, students were able to overcome these obstacles and contribute to cultural preservation and local economic development.